Harnessing tacit Knowledge from Sustainable Product Engineering through Artificial Intelligence - Mansheim, Johanna; Gräßler, Iris; Pfeifer, Jan Niklas (1st International Symposium: March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University)
Tacit knowledge is particularly valuable in product engineering. Experiences reside in minds of employees and are not systematically documented but could have a significant influence on sustainable product engineering. Existing approaches do not offer sufficient support for harnessing technical tacit knowledge regarding sustainable product engineering. In this paper a three-step method is presented: The method contains knowledge acquisition, requirements extraction und requirements validation for quality assurance. Acquisition is performed by support artifacts like interview guidelines. Extraction is supported by Artificial Intelligence, converting statements into requirements. These requirements are validated using a specific questionnaire. The developed approach is applied in a funded project of the European Union (EU) with automotive industry partners. The method supports product engineers to collect tacit knowledge from experienced employees, transform unsystematic knowledge into standardized technical requirements and validate them. Application of this method enables creation of validated requirements that can be applied throughout the company and are not exclusively dependent on a single employee.
Keywords: Tacit knowledge; Sustainability; Product Engineering; Artificial Intelligence

Continuous value shaping: A boundary concept for innovating service innovation approaches - Böhmann, Tilo; Roth, Angela; Satzger, Gerhard; Benz, Carina; Beverungen, Daniel; Boes, Andreas; Breidbach, Christoph; Gersch, Martin; Gudergan, Gerhard; Hogreve, Jens; Kurtz, Christian; Langes, Barbara; et al. (Electronic Markets)
Technological advancements and evolving value orientations reshape future value creation and pose new requirements for service innovation. While a variety of disciplines are developing new approaches to drive service innovation, this is primarily done in isolation and generates only fragmented solutions. Sociological theory has proposed “boundary objects” as an effective umbrella for communication and cooperation among communities. Therefore, we introduce continuous value shaping (CVS) as a boundary object describing service innovation approaches along five principles. We reflect on this concept through the different disciplinary lenses of researchers in service marketing, information systems, service engineering, sociology of work, and innovation management. These perspectives highlight how the CVS principles already connect to discourses within the individual disciplines. However, the CVS concept will not only provide an umbrella to embrace existing activities in different academic disciplines. It also assists to identify research themes that will benefit from uniting the power of these disciplines, and it can serve as an integrating framework to conceptualize complex service innovation approaches. Thus, the CVS concept should guide both researchers and practitioners to develop and implement novel innovation and transformation efforts—in and across organizations.
Keywords: Continuous value shaping (CVS); Service research; Service innovation; Digitalization; Sustainability; Interdisciplinary research

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Decentralized production concepts for bio-based polymers - implications for supply chains, costs, and the carbon footprint - Riese, Julia; Fasel, Henrik; Pannok, Maik; Lier, Stefan (Sustainable Production and Consumption)
Keywords: Industrial and Manufacturing Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry; Environmental Engineering

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (17th CIRP Conference on Intelligent Computation in Manufacturing Engineering)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy

Prospective Life Cycle Assessment of Lightweight Structures in Vehicles for On-Demand Mobility Systems - Ostermann, Moritz; Marten, Thorsten; Tröster, Thomas (16th Biennial International Conference on EcoBalance)
Keywords: Life Cycle Sustainability Assessment; Prospective Life Cycle Assessment; Life Cycle Engineering; On-Demand Mobility; Mobility Services

Assessment of Energy Efficiency and Flexibility Measures in Electrified Process Heat Generation Based on Simulations in the Animal Feed Industry - Knorr, Lukas; Schlosser, Florian; Meschede, Henning (Journal of Sustainable Development of Energy, Water and Environment Systems)
Keywords: Energy Engineering and Power Technology; Water Science and Technology; Environmental Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Hybrid renewable energy utility systems for industrial sites: A review - Walmsley, Timothy Gordon; Philipp, Matthias; Picón-Núñez, Martín; Meschede, Henning; Taylor, Matthew Thomas; Schlosser, Florian; Atkins, Martin John (Renewable and Sustainable Energy Reviews)
Keywords: Renewable Energy; Sustainability and the Environment

Carbon insetting as a measure to raise supply chain energy efficiency potentials: Opportunities and challenges - Ebersold, Felix; Hechelmann, Ron-Hendrik; Holzapfel, Peter; Meschede, Henning (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Decision support tool to determine the suitability of demand side management implementation in continuously operated processes – A biorefinery case study - Röder, Lilli; Etzold, Hendrik; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Biofuels, Bioproducts and Biorefining)
Abstract The time‐dependent adjustment of a system's power demand simultaneously with current power generation is commonly referred to as demand side management (DSM). DSM strategies are based on the flexibility to purchase electricity at times when prices are low, which can result in monetary benefits. One option to increase the flexibility of continuously operated processes is to oversize them. From an economic point of view, this leads to an increased investment. DSM only serves an economic purpose if the monetary benefits exceed this increase in capital costs. The main goal of this contribution is to develop a decision support tool to help evaluate unit operations regarding their feasibility for DSM implementation. In a case study, the decision support tool was applied to show its functionality on a biomethane production plant. The results show that with the help of the decision support tool, evaluating unit operations concerning their economic DSM potential is possible.
Keywords: Renewable Energy; Sustainability and the Environment; Bioengineering

CONSIDERING ENGINEERING ACTIVITIES AND PRODUCT CHARACTERISTICS TO ACHIEVE MATERIAL CIRCULARITY BY DESIGN - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Abstract To select design guidelines engineers have to identify relevant from a bewildering amount of design guidelines. In this paper, a rule-based method for selecting design guidelines for material circularity selection is presented. For this purpose, a generic Product Life Cycle model is detailed with regard to Multi Material cycles (gPLC-MM). The presented method is divided into four steps. Core of the presented method is the comparison of circular product strategies with product life phases and material recovery processes. Engineering activities and increments of the product architecture are used to identify design guidelines. The results show that through the material circularity-oriented design guideline identification method, the product architecture is designed for different processes and technologies, to recover materials. The method allows engineers to select guidelines in a more targeted and consolidated way in sustainability-friendly product engineering.
Keywords: Sustainability; Circular economy; Conceptual design

Work in Progress: Development of a Virtual and Interactive Microgrids Learning Environment for Microgrids Sustainability – The case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (Learning in the Age of Digital and Green Transition. ICL 2022. Lecture Notes in Networks and Systems)
Partial coverage of the traditional grid is one of the factors that con-tribute to the low electrical energy access levels in developing countries. This often results in long distances between the grid and unconnected communities. Microgrids, due to their distributed energy resources, have the potential to increase energy access levels. However, there is limited access to microgrids-related knowledge. The knowledge is essential for the effective and efficient use of energy, operation, and hence sustainability of microgrids. To contribute to the sustainability of microgrids, a Virtual and Interactive Microgrids Learning Environment (VIMLE) for microgrids knowledge transfer is developed. VIMLE development is guided by design-based research. With knowledge transfer and skills acquisition through the use of VIMLE, local capacity for designing, installing, operating and maintenance of microgrids is built. Skilled local capacity will contribute to microgrids sustainability. Hence, improve electrical energy access levels and contribute to the achievement of SDG 7.
Keywords: Knowledge Transfer; Microgrids; Sustainability

Geographic Information Systems in Information Systems Research - Review and Research Prospects - Priefer, Jennifer (Proceedings of the 56th Hawaii International Conference on System Sciences)
Since historical times, cartographic maps have revealed spatial relations and enabled decisions and processes. Geographic Information Systems (GIS) allow for acquisition, management, analysis, and presentation of geospatial objects. With free geospatial data becoming available through open data policies and an increasing amount of digitally connected objects in the Internet of Things (IoT), GIS are becoming indispensable to Information Systems (IS) research. However, the consideration and relevance of GIS has only been investigated rarely. We examine, how and in which fields of application GIS have been studied in the IS literature and elicit the importance of GIS regarding their design and usage. A systematic literature review leads us to develop four research propositions. Our results indicate that GIS are still an undeservedly underrepresented discipline in IS and should be more theorized, put center-stage in design-oriented research, and considered for creating superior value co-creation in service systems.
Keywords: GIS; Industry 4.0; and Sustainability; geographic information systems; geospatial data; gis; information systems research; literature review

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Creating water-in-salt-like environment using coordinating anions in non-concentrated aqueous electrolytes for efficient Zn batteries - Gomez Vazquez, Dario; Pollard, Travis P.; Mars, Julian; Yoo, Ji Mun; Steinrück, Hans-Georg; Bone, Sharon E.; Safonova, Olga V.; Toney, Michael F.; Borodin, Oleg; Lukatskaya, Maria R. (Energy & Environmental Science)
By using coordinating anions such as acetate, a water-in-salt-like coordination environment of Zn ions is achieved in relatively dilute conditions, leading to prolonged and efficient cycling of zinc metal anodes.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

Break-even of high-temperature heat pump integration for milk spray drying - Schlosser, Florian; Zysk, Sebastian; Walmsley, Timothy G.; Kong, Lana; Zühlsdorf, Benjamin; Meschede, Henning (Energy Conversion and Management)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Design approach to extend and decarbonise existing district heating systems - case study for German cities - Divkovic, Denis; Knorr, Lukas; Meschede, Henning (International Journal of Sustainable Energy Planning and Management)
This paper aims to present an approach for the planning of carbon low heat supply in a future district heating system based on open data for German cities with existing district heating networks. One focus is on the integration of industrial waste heat and the uncertainty of future waste heat sources as well as restrictions on the use of biomass. For that purpose, knowledge about the energy demand is necessary. In a first step it is shown how the demand around a heating network is estimated with spatial data and a load profile is generated. Local available heat sources are examined according to their suitability and their kind of integration in the heating network. As heat production from different units are optimised, the development of a simulation model will be presented. The simulation is based on the optimisation of the operational costs of the used technologies for heating supply. Different scenarios covering various technologies and economic assumptions are applied. The results show the levelized costs of heating as well as the ecological performance. A sensitivity analysis shows the importance of uncertainties for the economic assumptions. The results showing levelized costs of heating as well as the ecological performance underlining the advantage of excess heat integration.
Keywords: Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Ecological and Economic Feasibility of Inductive Heating for Sustainable Press Hardening Processes - Pfeifer, Florian; Knorr, Lukas; Schlosser, Florian; Marten, Thorsten; Tröster, Thomas (Journal of Sustainable Development of Energy, Water and Environment Systems)
Keywords: Energy Engineering and Power Technology; Water Science and Technology; Environmental Science (miscellaneous); Renewable Energy; Sustainability and the Environment